Efektivitas Pengawasan Internal Kejaksaan dalam Mewujudkan Integritas dan Akuntabilitas: Perspektif Negara Hukum Indonesia (HORIZON: Indonesian Journal of Multidisciplinary, 2025)
This study aims to analyze the effectiveness of internal supervision at the Attorney General's Office of the Republic of Indonesia, identify factors that hinder its implementation, and formulate directions for strengthening supervisory institutions. The method used is normative juridical with legislative, conceptual, and comparative approaches. Legal materials include Law Number 16 of 2004 jo. Law Number 11 of 2021 concerning the Attorney General's Office and regulations related to internal supervision. The analysis of legal materials was conducted in a prescriptive-analytical manner through the stages of inventory, identification of legal issues, systematization, and interpretation. The research results indicate that supervision by the Deputy Attorney General for Supervision (JAM-Was) has not been effective due to weak functional independence, inconsistency in disciplinary enforcement, a closed organizational culture, and fragmentation of internal and external supervision mechanisms. This study concludes that strengthening internal supervision in the Attorney General's Office requires enhancing the institutional independence of JAM-Was, reinforcing the whistleblowing system, digitalizing supervision, and creating synergy among supervisory agencies to realize an Attorney General's Office that is integrative and accountable.